The Influence of Profitability on Tax Avoidance (Empirical Study on Manufacturing Companies in the Basic and Chemical Industry Subsectors Listed on the Indonesia Stock Exchange 2018-2022 - Krisdina, Tiana Fenny; Masruri, Fahrul Alam; Riyanti, Kartika (Journal of Business, Accounting and Finance, 2024)
This study aims tp analyze the effect of profitability on tax avoidance empirical study in manufacturing companies in the basic and chemical industry sub-sectors listed on the indonesian stock exchange (BEI) 2018-2022 for the descriptive and verification approaches. The population of this study are manufacturing companies in the basic and chemical industry sub-sectors listed on the IDX for the 2018-2022 period, with purposive sampling method, in which the are 29 manufacturing companies in the basic and chemical industry subsector that meet the sample criteria with a five year observation method. Based on the test result showed that profitability with ROA measurement has no significant effect on tax avoidance with CETR measurement is avidenced by the value of 0,100 > 0,05 and the value -thitung < ttabel is -1,656 < 1,977 then H0 is accepted. Profitability with ROE measurement has no significant effect on tax avoidance with CETR measurement is evidenced by the value of 0,157 > 0,05 and the value thitung < ttabel is 1,422 < 1,977. Meaning that profitability with ROE does not have a significant effect on manufacturing companies in the basic and chemical industries subsector listed on the Indonesia Stock Exchange in 2018-2022.